Pengaruh Penerimaan Pajak Hotel, Pajak Restoran, Pajak Hiburan, Pajak Penerangan Jalan dan Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Batu : (Studi Kasus Pada Badan Keuangan Daerah Kota Batu Tahun 2012-2018). - Lesmana, Budi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
Indonesia as a government that adheres to the principle of regional autonomy, each region is given the authority to regulate its own government. Where to organize their own local government requires a source of income. One source of local revenue is local taxes and regional levies. The purpose of this study was to determine the effect of hotel taxes, restaurant taxes, street lighting taxes and advertisement taxes on local revenue This type of research is quantitative with a descriptive approach. The data used in the secondary data research contained in the Batu City regional financial institutions are in the form of regional tax target and realization reports and 2012-2018 regional original revenue target and realization reports. The research method used is multiple linear regression analysis to see the effect of hotel taxes, restaurant taxes, entertainment taxes, street lighting taxes and advertisement taxes on local revenue. The results of testing the hypothesis using the t test succeeded in proving that the hotel tax did not have a significant effect on local revenue, while the restaurant tax, entertainment tax, street lighting tax and advertisement tax had a significant effect on regional original income. The test results using the f test prove that the hotel tax, restaurant tax, entertainment tax, street lighting tax, and advertisement tax simultaneously affect local revenue. Keyword: Regional Autonomy, Revenue, Regression Analysis, Taxes, Realization Report.